Analysis of Segmentation, Reasons and Interests of Visiting Patients in the Inpatient Room at RSUD Genteng Banyuwangi City - Lia Retno Wulan Sari; Nurwijayanti Nurwijayanti; Sandu Siyoto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Hospital health services today undergo a fundamental change, namely to become a business entity with several strategic business units that require handling with the right management concept. In order to be able to sell services that are in accordance with market conditions. The purpose of the study is to find out the patient segmentation and the reasons for patients visiting the hospital and the interest of patients returning to the Banyuwangi Hospital. The research design was Cross Sectional. The population is all inpatients. The sample size is 144 respondents using Simple Random sampling technique. Independent variable is Segmentation. The dependent variable is the reason for the patient to visit and the interest in revisiting. Data were collected using a questionnaire, data were analyzed using logistic regression test (α ≤ 0.05). The results showed that the largest segmentation variable, namely the marital status variable did not affect the interest in revisiting (p = 0.849), and the residential variable did not affect the interest in revisiting (p = 0.698). Whereas the reason for visiting the biggest variable, namely the price variable does not affect the interest in revisiting (p = 0.628), the place variable does not affect the interest in revisiting (p = 0.531), and the people variable does not affect re-interest (p = 0.722). Segmentation and patient reasons have no effect on interest in revisiting. The quality of service at the hospital must provide satisfying and attractive services to attract patients to return to visit